Transcriptome analysis reveals ABA involved in the detoxification mechanism of macroalga Gracilariopsis lemaneiformis to cadmium toxicity - Xiaojiao Chen; Yueyao Tang; Xue Sun; Hao Zhang; Nianjun Xu (Frontiers in Marine Science, 2024)
IntroductionCadmium (Cd) is a significant threat environmental pollutant in the marine ecological environment offshore. The macroalga, Gracilariopsis lemaneiformis, of significant economic value, is widely cultivated along China’s coastline. Yet, little is known about the molecular mechanisms underlying Cd tolerance in macroalga.MethodsHere, we examined the transcriptome of G. lemaneiformis exposed to Cd to identify the responses to Cd stress.Results and discussionOur findings revealed that Cd led to the retardation of growth rate in G. lemaneiformis, accompanied by a notable reduction in the content of photosynthetic pigments and a decrease in the expression of genes associated with the photosynthetic system and nitrogen metabolism. When exposed to Cd, there was a rapid increase in Cd levels through the upregulation of genes encoding GlZIP6 and GlIRT1. Additionally, the expression of Cd efflux transporters, GlZIP1 and GlABCG22, and the ABCC7 transporter for compartmentation to the vacuole, was induced to mitigate Cd toxicity. Cd also activated crucial genes involved in the ABA biosynthesis and enhanced ABA content, thereby inducing ABA signaling pathway. Furthermore, exogenous ABA reduced the growth inhibition of G. lemaneiformis under Cd stress. Redox homeostasis was adjusted to adapt to Cd toxicity, with thioredoxin, glutaredoxin cycle and ascorbate-glutathione cycle identified as playing significant in maintaining reactive oxygen species homeostasis. Moreover, transcription factors such as several MYBs, signal transmission factors G protein and heat shock proteins (sHSPs, HSP 40, HSP 90, HSP101) were involved in the detoxification of Cd. Collectively, this study provided a comprehensive understanding of the molecular mechanisms underpinning the of responses of macroalga G. lemaneiformis to Cd exposure.